Broad and potent activity against SARS-like viruses by an engineered human monoclonal antibody - Rappazzo, C. Garrett; Tse, Longping V.; Kaku, Chengzi I.; Wrapp, Daniel; Sakharkar, Mrunal; Huang, Deli; Deveau, Laura M.; Yockachonis, Thomas J.; Herbert, Andrew S.; Battles, Michael B.; O’Brien, Cecilia M.; Brown, Michael E.; et al. (Science (American Association for the Advancement of Science), 2021)
As we continue to battle the COVID-19 pandemic, we must confront the possibility of new pathogenic coronaviruses emerging in humans in the future. With this in mind, Rappazzo et al. isolated antibodies from a survivor of the 2003 severe acute respiratory syndrome coronavirus (SARS-CoV), used yeast display libraries to introduce diversity into these antibodies, and then screened for binding to SARS-CoV-2. One of the affinity-matured progeny strongly neutralized SARS-CoV-2, SARS-CoV, and two SARS-related viruses from bats. In addition, this antibody bound to the receptor-binding domains from a panel of sarbecoviruses, suggesting broader activity, and provided protection against SARS-CoV and SARS-CoV-2 in mouse models. Science , this issue p. 823 An affinity-optimized human monoclonal antibody displays broad in vivo efficacy in murine models of SARS and COVID-19. The recurrent zoonotic spillover of coronaviruses (CoVs) into the human population underscores the need for broadly active countermeasures. We employed a directed evolution approach to engineer three severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies for enhanced neutralization breadth and potency. One of the affinity-matured variants, ADG-2, displays strong binding activity to a large panel of sarbecovirus receptor binding domains and neutralizes representative epidemic sarbecoviruses with high potency. Structural and biochemical studies demonstrate that ADG-2 employs a distinct angle of approach to recognize a highly conserved epitope that overlaps the receptor binding site. In immunocompetent mouse models of SARS and COVID-19, prophylactic administration of ADG-2 provided complete protection against respiratory burden, viral replication in the lungs, and lung pathology. Altogether, ADG-2 represents a promising broad-spectrum therapeutic candidate against clade 1 sarbecoviruses.